2001
DOI: 10.1001/jama.286.14.1754
|View full text |Cite
|
Sign up to set email alerts
|

Serial Evaluation of the SOFA Score to Predict Outcome in Critically Ill Patients

Abstract: Sequential assessment of organ dysfunction during the first few days of ICU admission is a good indicator of prognosis. Both the mean and highest SOFA scores are particularly useful predictors of outcome. Independent of the initial score, an increase in SOFA score during the first 48 hours in the ICU predicts a mortality rate of at least 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

98
1,696
17
74

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,352 publications
(1,962 citation statements)
references
References 21 publications
98
1,696
17
74
Order By: Relevance
“…Severity of illness at ICU admission was assessed using the acute physiology and chronic health evaluation (APACHE) version II score [21]. Severity of illness during ICU admission was estimated daily with the sequential organ failure (SOFA) score [22,23]. We further recorded daily the use of physical restraints at any moment during the preceding day, defined from 10 A.M. to 10 A.M.…”
Section: Data Collectionmentioning
confidence: 99%
“…Severity of illness at ICU admission was assessed using the acute physiology and chronic health evaluation (APACHE) version II score [21]. Severity of illness during ICU admission was estimated daily with the sequential organ failure (SOFA) score [22,23]. We further recorded daily the use of physical restraints at any moment during the preceding day, defined from 10 A.M. to 10 A.M.…”
Section: Data Collectionmentioning
confidence: 99%
“…Encouraging results have also been obtained in cancer patients requiring renal replacement therapy for acute renal failure, even in case of multiple organ failure or in combination with ventilatory support [33][34][35][36] . While renal replacement therapy was unequivocally associated with a 90-95% ICU mortality in case of multiple organ failure two decades ago 12,18 , Soares et al 31 recently reported 65% six month mortality in patients with one or two associated organ failures and a 93% six month mortality in case of 3 associated organ failures, again similar to general ICU patients 32 . Moreover, in a study by Benoit et al comparing the six-month survival between critically ill patients with and without hematological malignancy, the presence of an underlying hematological malignancy was not independently related with six-month survival once accounting for the severity of illness upon ICU admission or the duration of hospitalization prior to admission 33 .…”
Section: Outcome In Critically Ill Cancer Patients: Evolution Over Thmentioning
confidence: 97%
“…The high mortality of more than 80% in patients requiring mechanical ventilation (Table 1) [8][9][10][11][12][13][14][15] , increasing to more than 90% to 95% in patients developing multiple organ failure or who require renal replacement therapy during ICU stay 12,[16][17][18] , particularly in the transplant setting [19][20][21] , together with the severe emotional burden endured by these patients and their relatives, and the considerable costs of advanced and prolonged life-supporting therapy 13 resulted in a general reluctance to admit such patients to the ICU 2,6,7 . However, over the past few years, several centres throughout the world have been reporting on increasingly improving survival in critically ill patients with hematological malignancies and solid tumors [22][23][24][25][26][27][28][29][30][31] , approaching survival rates reported in general ICU patients 32 . In a case-historical control study 22 , Azoulay et al reported a four-fold lower risk of death in cancer patients who required mechanical ventilation between 1996 and 1998 as compared with 1990-1995.…”
Section: Outcome In Critically Ill Cancer Patients: Evolution Over Thmentioning
confidence: 99%
“…Di antara manfaat tersebut yaitu manfaat dalam penentuan pengambilan keputusan oleh tenaga medis dan keluarga, menentukan bentuk pendekatan dan perawatan yang terbaik bagi pasien, serta antisipasi dan alokasi dari penggunaan alat bantu (obat vasopresor, ventilator, dan hemodialisas) atau sumber daya lainnya. 14,15 Oleh karena itu, penelitian ini dilakukan dengan cara analisis kesintasan pada pasien sepsis berat berdasarkan perbedaan bersihan laktat. Dengan demikian, diharapkan hasil penelitian ini dapat digunakan untuk memberikan informasi klinis bagi tenaga medis, keluarga, dan pengambil keputusan lainnya untuk menentukan bentuk pendekatan tata laksana terbaik pada pasien, serta antisipasi dari keluaran yang mungkin terjadi.…”
Section: Pendahuluanunclassified